Game Therapy Based on Local Wisdom in Cognitive Development of Slow Learner Children - Fithriyana, Eshthih; Hidayah, Hidayah (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2019)
Early childhood is an important time for everyone. Because at this stage the child will experience very rapid development in various aspects of development. At this stage children also have the potential to experience problems that can inhibit their development, one of which is slow learner. The purpose of this study was to determine how local wisdom-based game therapy can develop the cognitive abilities of slow learner children. This type of research is qualitative research. The subjects of this study were the teacher and children of slow learners at RA Subulus Salam Bojonegoro and RA Nurul Ulum Bojonegoro. Data collection techniques using questionnaires, interviews and documentation. Based on the results of the coefficient and interview children slow learners experience several obstacles in cognitive development. Local wisdom-based therapy games help slow learners to practice their ability to understand certain commands or rules. Because local wisdom-based therapy games give children the opportunity to obtain information or commands that are concrete and more tangible